Hardness characterisation of grey cast iron and its tribological performance in a contact lubricated with soybean oil. (January 2018) - Bahari, Adli; Lewis, Roger; Slatter, Tom
The effect of hardness of grey cast iron flat specimen on its wear and friction on the contact were characterised with the presence of vegetable oil as biolubricant. Prior to the tribological test, the as-received grey cast iron flat specimen hardness was characterised. Friction and wear tests were then conducted using a ball-on-flat reciprocating sliding contact. The one-way analysis of variance (ANOVA) was used to determine the significance of friction and wear data with a 95% significance level. The wear scars after the test were then characterised by surface roughness and wear mechanism. The microstructure and elemental analysis were also reported. The average value of hardness was 210 HV with a large difference between minimum (185 HV) and maximum (250 HV) values. The friction and wear performance of grey cast iron specimens with soybean oil varied with its hardness. The specimens with higher hardness gave lower friction coefficient and greater wear resistance than the lower hardness specimens. The difference in coefficient of friction produced between high hardness specimens (COF = 0.122) and low hardness specimens (COF = 0.140) was 17%. In terms of mass loss, the low hardness specimens (mass loss = 50.38 mg) and the high hardness specimens (mass loss = 12.90 mg) produced a difference of 74%. It is shown that, with soybean oil lubricant, the grey cast iron specimen can produce wide range of tribological data especially on mass loss due to its hardness distribution. The influence of soybean oil lubrication in this work is less in improving the wear resistance (about 7%), but greater for friction reduction (about 24%) compared to an unlubricated grey cast iron surface. The hardness of grey cast iron specimen is an important parameter that needs to be specifically measured and controlled on the contact due to wide hardness distribution of grey cast iron may produce variation in tribological data.